Mitochondrial dihydrolipoyl dehydrogenase activity shapes photosynthesis and photorespiration of arabidopsis thaliana - Timm, Stefan; Wirtz, Markus; Hell, Rüdiger (The plant cell, 2015)
Mitochondrial dihydrolipoyl dehydrogenase (mtLPD; L-protein) is an integral component of several multienzyme systems involved in the tricarboxylic acid (TCA) cycle, photorespiration, and the degradation of branched-chain α-ketoacids. The majority of the mtLPD present in photosynthesizing tissue is used for glycine decarboxylase (GDC), necessary for the high-flux photorespiratory glycine-into-serine conversion. We previously suggested that GDC activity could be a signal in a regulatory network that adjusts carbon flux through the Calvin-Benson cycle in response to photorespiration. Here, we show that elevated GDC L-protein activity significantly alters several diagnostic parameters of cellular metabolism and leaf gas exchange in Arabidopsis thaliana. Overexpressor lines displayed markedly decreased steady state contents of TCA cycle and photorespiratory intermediates as well as elevated NAD(P)+-to-NAD(P)H ratios. Additionally, increased rates of CO2 assimilation, photorespiration, and plant growth were observed. Intriguingly, however, day respiration rates remained unaffected. By contrast, respiration was enhanced in the first half of the dark phase but depressed in the second. We also observed enhanced sucrose biosynthesis in the light in combination with a lower diel magnitude of starch accumulation and breakdown. These data thus substantiate our prior hypothesis that facilitating flux through the photorespiratory pathway stimulates photosynthetic CO2 assimilation in the Calvin-Benson cycle. They furthermore suggest that this regulation is, at least in part, dependent on increased light-capture/use efficiency.